(untitled) (Al-Qamar, 2026)
This research article critically examines the well-known narration attributed to Hazrat Umar bin Khattab (RA) regarding the limitation of mahr (dower). Certain groups have used this report to question his juristic understanding; therefore, this study focuses on evaluating the authenticity of the narration through a detailed analysis of its chain of transmission (sanad) and textual content (matan). By reviewing the opinions of classical scholars of hadith and examining the reliability of the narrators, the study demonstrates that the narration suffers from weaknesses such as disconnection in the chain and unreliable transmitters, which render it academically questionable. The article further clarifies the scholarly responses to the objections raised on the basis of this report and highlights that such weak narrations cannot be used to cast doubt on the personality and juristic authority of Hazrat Umar (RA). Ultimately, the study contributes to a clearer understanding of the issue by presenting a balanced scholarly evaluation of the narration.